Modeling and Simulation for Propylene Present in Exhaust Gas using a Monolithic Catalytic Converter - Chauhan, Sanchita (Asian Journal of Chemistry, 2010)
Numerical simulation is carried out for reducing the concentration of hydrocarbon propylene present in exhaust. Catalytic converter monoliths are used to bring a faster reduction of propylene at a much lower temperature. Model equations are proposed to calculate the concentration and temperature of the gas, along with catalyst temperature during the warm-up period.